O papel do(a) professor(a) coordenador(a) pedagógico(a) na formação em serviço dos(as) docentes do ensino fundamental II: uma análise dessa função em uma rede municipal de ensino do interior paulista - Oliveira, Carolina Alves de (Universidade Federal de São Carlos, 2018)
This research defends the importance of pedagogical coordinator teacher as former of the school team, due to the complexity of its functions and its commitment to the learning and formation processes of the teachers, as well as the students. In this sense, the objective of the study is to analyze the role of the coordinating teacher in the Collective Pedagogical Work Schedules (HTPCs) and the reflexes of their actions in the continuous and reflexive formation of the teachers who work in the years of elementary school (6th to 9th grade) in a municipal school network in the interior of São Paulo. As specific objectives, this study aims to: understand the role played by the coordinating teacher with its peers; analyze the understanding of these professionals about continuing education; identify how they select the topics to be worked on in HTPC meetings with teachers from different areas of knowledge; raise and describe the deliberations and actions of the Municipal Department of Education (SME), regarding the guidelines and training for the work of the coordinator teachers in the schools; investigate how these professionals encourage the active participation of the group of teachers, both as regards planning and the development in practice of these meetings of HTPCs. The research of qualitative nature was carried out by means of a bibliographical survey about the researched topic and the application of questionnaires to 7 (seven) coordinating teachers who work in the final years of elementary education (6th to 9th grade) of a network education of the interior of São Paulo. The data were grouped into four axes: a) Performance of the pedagogical coordinator teacher; b) Continuing and in-service training; c) Reflection on practice; d) Formative processes and knowledge. The research results show that they are experienced professionals in teaching; they consider themselves responsible for the continued formation of their teams; they point out the difficulties and obstacles in the performance of their functions, ranging from the lack of adequate training (both initial and continued) to deviation from their functions and meeting daily and bureaucratic emergency demands; they affirm that the HTPC is the largest space for training and dialogue with peers; they establish a good relationship with school management; they reveal that do not have autonomy, because the actions are decreed by the several superior instances; they understand the need for continuity of studies and updating; they highlight the lack of training and conceptual understanding about a reflexive practice, although they develop actions focused on dialogue, criticality and respect for the group; they evidence do not feel prepared to perform the job, because of the lack of courses, training and support from the SME. In this sense, we defend the importance of new research and studies in the area, with the purpose of contributing to the improvement of the initial and continuing training courses for actions linked to the Municipal Departments of Education, as well as for the improvement of the working conditions of pedagogical coordinator teacher.
The role of the pedagogical coordinator (a) teacher in the in-service training of teachers of fundamental teaching II: an analysis of that function in a municipal network of teaching of the paulista interior
Keywords: Professores; Coordenadores educacionais; Ensino fundamental; Horário de Trabalho Pedagógico Coletivo (HTPC); Formação continuada e em serviço; Reflexão sobre a prática; Teachers; Pedagogical coordinator; Elementary school; Collective Pedagogical Work Schedule (HTPC); Continuing and in-service training; Reflection on practice; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM